How they swam: The evolution of the crawl stroke - Carlile, F.
The article is on the evolution to the modern crawl stroke. Coach Carlile used video and films showing the technique of World Championship Freestyle swimmers from 1890 to present day. He did not separate the distance and sprint freestyle swimmers, even though he recognizes that their training is different and their technique can be a reflection of this.